Downscaling Water Relevant Sustainable Development Goals to Region (Country), Basin, and Local Scale - Cai, Ximing (2023)
Ximing Cai POLICY SEMINAR Water & SDGs - Downscaling WATer relevant SDGs (DWAT-SDGs) 2023 UN Water Conference Side Event Jointly organized with the International Water Resources Association (IWRA) MAR 20, 2023 - 10:00 TO 11:00AM EDT